ANALISIS PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA (STUDI PADA DINAS PERTANIAN, KELAUTAN DAN PERIKANAN KOTA MATARAM) - Lilik Sundasari; Zainal Abidin (Master of Management, Mataram University, 2016)
This research entitles Analysis of the Effect of Work Environment and Compensation to the Work Satisfaction (A Study at the Department of Agriculture, Marine and Fishery of Kota Mataram). It is aimed at analyzing the effect of physical work environment, non-physical work environment and compensation to the work of the staffs at the Department of Agriculture, Marine and Fishery of Kota Mataram, both simultaneously and partially. This particular research is an associative research. Those surveyed are 103 staffs in total who are employed as civil servants at that particular department. The sample of the research was selected using total sampling technique, in which it took all civil servants as respondents. The instruments were examined using multiple linier regression analysis method, in which the software SPSS 20 was used to examine research hypothesis. The research reveals that ,(1) physical. non-physical work environment and compensation partially effected the staffs’ work satisfaction significantly, (2) physical. non-physical work environment and compensation simultaneously effected the staffs’ work satisfaction significantly, (3) physical work environment effected the staffs’ work satisfaction dominantly. Key words: Physical Work Environment, Non-Physical Work Environment, Compensation and Work Satisfaction